Anomalous Correlation between Dielectric Constant and Tunability in (Ba, Sr)TiO3–MgO–Mg2SiO4 Composite Ceramics. Issue 4 (25th January 2013) - He, Yanyan; Zhao, Jingyuan; Xu, Yebin; Li, Changnian; Randall, C.
<x xml:space="preserve">Abstract</x> (Ba, Sr)TiO3–MgO–Mg2SiO4 composite ceramics were prepared by a solid‐state reaction method. The microstructures, microwave dielectric characteristics, and tunability of composite ceramics were investigated. An anomalous correlation between tunability and dielectric constant was observed: with the increase in Mg2SiO4 content and the decrease in MgO content, the dielectric constant of (Ba, Sr)TiO3–MgO–Mg2SiO4 composite ceramics decreases, but the tunability increases. The anomalous increased tunability is beneficial for tunable microwave applications and can be attributed to the redistribution of the electric field. For 50Ba0.5Sr0.5TiO3–(50−x)MgO–xMg2SiO4, the dielectric constant was decreased from 164.2 to 126.5 by increasing Mg2SiO4 content from 5 to 45 wt% and the tunability at 3.9 kV/mm increased from 11.5% to 15.2%.